2014
DOI: 10.1038/bjc.2014.530
|View full text |Cite
|
Sign up to set email alerts
|

Time dependence of biomarkers: non-proportional effects of immunohistochemical panels predicting relapse risk in early breast cancer

Abstract: Background:We investigated the impact of follow-up duration to determine whether two immunohistochemical prognostic panels, IHC4 and Mammostrat, provide information on the risk of early or late distant recurrence using the Edinburgh Breast Conservation Series and the Tamoxifen vs Exemestane Adjuvant Multinational (TEAM) trial.Methods:The multivariable fractional polynomial time (MFPT) algorithm was used to determine which variables had possible non-proportional effects. The performance of the scores was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Eleven separate validation cohorts 24,25,58,73,74,77,[122][123][124][125][126][127][128][129] have reported prognostic performance data for IHC4, with a total of 13,434 patients. 127 and the study from Taiwan.…”
Section: Prognostic Performance: Ihc4 and Ihc4+cmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven separate validation cohorts 24,25,58,73,74,77,[122][123][124][125][126][127][128][129] have reported prognostic performance data for IHC4, with a total of 13,434 patients. 127 and the study from Taiwan.…”
Section: Prognostic Performance: Ihc4 and Ihc4+cmentioning
confidence: 99%
“…124 TransATAC, 46 WSG PlanB, 73,74,77 GEICAM 9906, 129 WSG-AGO-Doc, 123 the Kaiser Permanente cohort, 125 the Institut Curie 128 cohort and the Chinese 58 cohort all recruited or reported a subgroup of HER2-patients. Only one validation cohort (Stephen et al 126 ) treated 100% of patients with endocrine monotherapy, and the remainder treated varying proportions of patients with endocrine therapy and chemotherapy. Two observational studies were from East Asia; 58,124 clinical advice received by the EAG suggests that these two East Asian studies may be less generalisable to the English context because (1) patients were treated in accordance with usual clinical practice and this may differ between these countries and England enough to affect prognostic outcomes and (2) it is possible that people of different ethnicities have different underlying risk profiles and disease natural histories.…”
Section: Prognostic Performance: Ihc4 and Ihc4+cmentioning
confidence: 99%
“…It was developed from a retrospective analysis of 1125 patients with ER-positive disease from the TransATAC cohort who did not received chemotherapy, validated in an independent cohort of 786 patients and has been shown to perform similarly to the Genomic Health recurrence score (RS) in predicting distant recurrence ( Cuzick et al , 2011 ). In this journal, Stephen et al , 2014 showed that in an endocrine treated population from the TEAM trial, the IHC4 provided stronger prognostic information when compared with the Mammostrat score.…”
mentioning
confidence: 99%
“…In the 915 patients, the authors examined the likelihood ratio for both IHC4 and BCI; IHC4 appeared prognostic for recurrence to 5 years in multivariable analysis. Stephen and colleagues also showed that IHC4 was prognostic to 5 years using independent Cox analysis in samples from the Edinburgh BCI series and TEAM trial . However, others have shown that a nomogram constructed from St. Gallen guidelines and Adjuvant Online (AOL), combined with IHC4 + CTS, provides prognostic information beyond that from IHC4 + CTS alone …”
Section: Resultsmentioning
confidence: 99%